1989
DOI: 10.1111/j.1365-3180.1989.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of maize and sorghum to four different safeners for metazachlor

Abstract: The ability of the herbicide safeners. BAS-145138 (I "dichloroaL;etyl-hex.iihydrt)-3,3,8a-irimethylpyrrolo( 1.2a)pyrimidin-6(2/D-one), dichlormid (A'.N-dialIyl-2,2-diehloroacelamide), ilurazoie (phenylmethyl ester), and MG-191 (2-dichloromelhyl-2-metliyl-l.3-dioxolane) for preventing metazachlor Injury to maize (Zea mays L.) and sorghum (Sorghum hicotor L.) seedlings were compared with their effects on '""C-metazachlor metabolism lo a glutathione (GSH) conjugate, effects on non-protein thiol contents (mainly G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…2B). In this mixture, five other active compounds can form adducts with GSH (Ekler and Stephenson, 1989;Tal et al, 1993;Prade et al, 1998) and a loss of effect could also result of their conjugation to GSH through GSTs induction by BE.…”
Section: Effect Of Mixtures In Relation To the Presence Of The Safenermentioning
confidence: 99%
“…2B). In this mixture, five other active compounds can form adducts with GSH (Ekler and Stephenson, 1989;Tal et al, 1993;Prade et al, 1998) and a loss of effect could also result of their conjugation to GSH through GSTs induction by BE.…”
Section: Effect Of Mixtures In Relation To the Presence Of The Safenermentioning
confidence: 99%
“…Metazachlor was also registered for use in maize in South Africa for some years. It is selective in maize when applied with a safener (Ekler & Stephenson, 1989). Lack of stable selectivity for maize led to the withdrawal of this herbicide from the South African market in 1999.…”
Section: Introductionmentioning
confidence: 97%
“…], sugarcane (Saccharum officinarum L.) and tobacco (Nicotiana tabacum L.). It is mainly used for the control of annual grass weeds and some broad leaf weeds (BASF, 1984;Ekler & Stephenson, 1989;Tomlin, 1994;Vermeulen et al, 1998). Metazachlor was also registered for use in maize in South Africa for some years.…”
Section: Introductionmentioning
confidence: 98%
“…Several new dichloroacctamide safeners MON-13900, MON-4660, BAS-145138 {1-dichloroacetylhexahydro-3,3-8atrimcthyl-pyrrolo[ 1,2-a}pyrimidin-6-(2/1) -0 n e }, and CGA-154281 have recently been developed to increase corn tolerance to acetochlor, alachlor, 1l1ctolachlor, and mctazach 1or (2-chloro-N-(2,6-dimethylphcnyl)-N-( IHpyrazol-I-ylnlcthyl)acetamide), respectively. These~ichloroacetarnide safeners have demonstrated a potential for increasing corn tolerance to a variety of chloroacetanilides (4,5,16,20,25,26) as well as other hcrhicide chclnistrics (3). Although studies have shown that these safeners increase corn, but not sorghum (5,8), tolerance to chloroacetanilide herbicides, only a linlitcd alnount of work has been done to exallline their performance under conditions conducive to chloroacctanilide injury and in combination with other herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…These~ichloroacetarnide safeners have demonstrated a potential for increasing corn tolerance to a variety of chloroacetanilides (4,5,16,20,25,26) as well as other hcrhicide chclnistrics (3). Although studies have shown that these safeners increase corn, but not sorghum (5,8), tolerance to chloroacetanilide herbicides, only a linlitcd alnount of work has been done to exallline their performance under conditions conducive to chloroacctanilide injury and in combination with other herbicides. Therefore, the objectives of these studies were to detertnine: whether MON-4660, CGA-154281, dichlornlid, and MON-13900 would increase alachlor, metolachlor, and acetochlor tolerance in corn grown at different soil temperatures~the effect of dicanlba.…”
Section: Introductionmentioning
confidence: 99%